Rayleigh Wave Propagation With Rotation, Two Temperature With Diffusion in Context to Dual Phase Lag Thermoelasticity - Thakur, Bharti; Kumari, Sangeeta; Kumar, Ashwani (Communications in Mathematics and Applications, 2023)
In the present paper, the theory of generalized thermoelasticity projected by Lord and Shulman (LS) [29] is used to originate the frequency equation for Rayleigh Wave (RW) through rotating isotropic Dual Phase Lag (DPL) with 2-temperature thermo-elastic medium with diffusion. The methodology of surface wave solution is deployed to solve these equation, further these equations are summarized to isotropic case in xz-plane. The characteristic equation related to speed of Rayleigh Wave (RW) is also obtained in context to the suitable boundary conditions and is solved for half space using programming. Some significant results are also concluded in the present study in a half space. The effects of various parameters in the present problem such as 2-temperature, rotation, dual phase lag, frequency and diffusion on the wave speed of Rayleigh wave is depicted by graph.
Keywords: Generalized thermoelasticity; Rayleigh Wave (RW); Rotation; 2-temperature; Diffusion; Wave speed; Dual-Phase Lag (DPL); Secular equation